2015
DOI: 10.1016/j.joto.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcript variants and expression profiles analysis of Mitf gene in minipigs

Abstract: ObjectTo identify transcript variants and expression patterns of porcine Mitf.Materials and methodsA pairwise BLAST search at NCBI database was performed to deduce the structure of porcine Mitf gene. Subsequently, 5′ RACE and fluorescent quantitative RT-PCR were used to analyze the expression pattern of porcine Mitf in different tissues.ResultsFour transcript variants of porcine Mitf, MITF-A, MITF-H, MITF-M and MITF-SUS were identified, all sharing high homology with those in humans, except Mitf-SUS.Conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…(2016) found that a mutation of MITF-M led to early degeneration of stria vascularis intermedia cells in the cochlea, as well as depigmentation, similar to the typical human Waardenburg syndrome phenotype. Guo ( Guo et al., 2015b ) et al. Studied transcription variation and expression patterns of the porcine MITF gene, and found a high degree homology between porcine and human MITF sequences.…”
Section: Resultsmentioning
confidence: 99%
“…(2016) found that a mutation of MITF-M led to early degeneration of stria vascularis intermedia cells in the cochlea, as well as depigmentation, similar to the typical human Waardenburg syndrome phenotype. Guo ( Guo et al., 2015b ) et al. Studied transcription variation and expression patterns of the porcine MITF gene, and found a high degree homology between porcine and human MITF sequences.…”
Section: Resultsmentioning
confidence: 99%